Inclusive and Effective Citizen Engagement : Participatory Budgeting--Makueni and West Pokot Counties - World Bank Group (World Bank, Washington, DC, 2017)
The introduction of citizen engagement into law is an idea that is gaining popularity around the world. New provisions in Kenya’s Constitution enshrine openness, accountability, and public participation as guiding principles for public financial management. Yet, translating participation laws into meaningful action on the ground is no simple task. With support from the Kenya participatory budgeting initiative (KPBI), and the commitment from West Pokot and Makueni County leaders, PB is being tested as a way to achieve more inclusive and effective citizen engagement processes while complying with national legal provisions. This report describes the PB approach being adopted by Makueni and West Pokot counties. It seeks to provide detailed information on the step by step process that the two Counties have adopted and describes the support provided by the KPBI. At the national level, the report is mostly targeted towards PB practitioners and county officials interested in introducing PB as part of their budgeting cycle. The report seeks also to inform a wider audience of PB and citizen engagement practitioners on the Kenyan experience to date.